Assessing the Potential Success of the People's Initiative on an Anti-Political Dynasty Act: Data from the Top Five Most Dynastic Philippine Provinces - Mendoza, Ronald U (Archīum Ateneo, 2014)
Efforts are now underway to mobilize support for a petition for the enactment of a national legislation on an Anti-Political Dynasty Act through people’s initiative. This is made possible by Article VI, Section 32 of the Constitution, that enables the public to propose a law “after the registration of a petition therefore signed by at least ten per centum [10%] of the total number of registered voters, of which every legislative district must be represented by at least three per centum [3%] of the registered voters thereof”. For this initiative to succeed, it requires gathering the signatures of nearly 5.2-million registered voters spread across the entire country. If successful, this would, in turn, pave the way for a referendum or plebiscite on an Anti-Political Dynasty Act. To help assess the prospects for collecting enough signatures in selected Philippine provinces, we turn to data on the 2013 elections. In particular, we examine the Mayoral votes in each of the municipalities in some of these provinces, in order to arrive at a rough barometer of potential support for the petition.